Trajectory of post-traumatic stress and depression among children and adolescents following single-incident trauma. Issue 1 (31st December 2022) - Zhang, Joyce; Meiser-Stedman, Richard; Jones, Bobby; Smith, Patrick; Dalgleish, Tim; Boyle, Adrian; Edwards, Andrea; Subramanyam, Devasena; Dixon, Clare; Sinclaire-Harding, Lysandra; Schweizer, Susanne; Newby, Jill; et al.
ABSTRACT: Objective: Post-traumatic stress disorder and depression have high comorbidity. Understanding their relationship is of clinical and theoretical importance. A comprehensive way to understand post-trauma psychopathology is through symptom trajectories. This study aims to look at the developmental courses of PTSD and depression symptoms and their interrelationship in the initial months post-trauma in children and adolescents. Methods: Two-hundred-and-seventeen children and adolescents aged between eight and 17 exposed to single-event trauma were included in the study. Post-traumatic stress symptoms (PTSS) and depression symptoms were measured at 2 weeks, 2 months and 9 months, with further psychological variables measured at the 2-week assessment. Group-based trajectory modelling (GBTM) was applied to estimate the latent developmental clusters of the two outcomes. Logistic regression was used to identify predictors associated with high symptom groups. Results: The GBTM yielded a three-group model for PTSS and a three-group model for depression. PTSS trajectories showed symptoms reduced to a non-clinical level by 9 months for all participants (if they were not already in the non-clinical range): participants were observed to be resilient (42.4%) or recovered within 2 months (35.6%), while 21.9% experienced high level PTSS but recovered by 9 months post-trauma. The depression symptom trajectories predicted a chronic non-recovery group (20.1%) and two mild symptom groups (45.9%, 34.0%). Further analysis showed high synchronicity between PTSS and depression groups. Peri-event panic, negative appraisals, rumination and thought suppression at 2 weeks predicted slow recovery from PTSS. Pre-trauma wellbeing, post-trauma anxiety and negative appraisals predicted chronic depression. Conclusions: Post-trauma depression was more persistent than PTSS at 9 months in the sampled population. Cognitive appraisal was the shared risk factor to high symptom groups of both PTSS and depression. HIGHLIGHTS: GBTM models estimated trajectories of PTS and depression symptoms from 2 weeks to 9 months posttrauma. PTSS trajectories were highly consistent with depression trajectories. Cognitive appraisal was the shared risk factor to high symptom groups in PTSS and depression.